Intracellular Accumulation and Secretion of YKL-40 (CHI3L1) in the Course of DMSO-Induced HL-60 Cell Differentiation - Izabela Jatczak-Pawlik; Alicja Ewiak-Paszyńska; Małgorzata Domowicz; Anna Jurewicz; Mariusz Stasiołek (MDPI AG, 2024)
YKL-40 (CHI3L1) is a matrix glycoprotein stored in human neutrophil-specific granules and released upon activation. While it is implicated in inflammation, cancer progression, and cell differentiation, its exact physiological role remains unclear. This study investigated the intracellular expression and secretion of YKL-40 by untreated and DMSO-treated HL-60 cells in association with surface expression of CD11b and CD66b throughout the differentiation process (up to 120 h). Secreted YKL-40 protein and mRNA levels of YKL-40, CD66b, and CD11b were measured by ELISA and quantitative RT-PCR, respectively. The intracellular YKL-40 and surface CD11b and CD66b expression were assessed by flow cytometry. A significant increase in CD11b expression confirmed DMSO-induced differentiation of HL-60 cells. Upon DMSO stimulation, YKL-40 mRNA expression increased in a time-dependent manner, unlike CD66b. The lack of CD66b (a granulocyte maturation and activation marker) on the surface of HL-60 cells might suggest that DMSO treatment did not induce full maturation or activation. The intracellular YKL-40 protein expression was increasing up to 96 h of DMSO treatment and then declined. YKL-40 secretion into the culture medium was detectable only at later time points (96 and 120 h), which was correlated with a decreased proliferation of DMSO-treated HL-60 cells. These findings suggest sequential changes in YKL-40 production and secretion during DMSO-induced differentiation of HL-60 cells and might contribute to a better understanding of YKL-40's involvement in both physiological processes and disease development, including multiple sclerosis.